Gray matter atrophy and disability progression in patients with early relapsing-remitting multiple sclerosis: a 5-year longitudinal study - Horakova, Dana; Dwyer, Michael G; Havrdova, Eva; Cox, Jennifer L; Dolezal, Ondrej; Bergsland, Niels; Rimes, Brett; Seidl, Zdenek; Vaneckova, Manuela; Zivadinov, Robert (Journal of the neurological sciences, 2009)
We assessed the relationship between gray matter (GM) and white matter (WM) atrophy and clinical status in early relapsing-remitting multiple sclerosis (MS) patients over 5 years. A group of 181 patients who participated in the ASA (Avonex-Steroid-Azathioprine) study and had complete clinical and MRI assessments over 2 and 5 years was investigated. One hundred seventy (170) patients completed the 12-month follow-up, 147 the 24-month, 98 the 36-month, 65 the 48-month and 47 the 60-month. Changes in GM (GMV), WM (WMV) and peripheral GM (PGV) volumes, whole brain volume (percentage brain volume change PBVC), lateral ventricle volume (LVV), third ventricle width (3VW) and T2-lesion volume (T2-LV) were measured. Patients were assigned according to their clinical status to one of two groups: the Stable group, and the Reached Confirmed Sustained Progression (RCSP) group (24-week interval). At 0-6 months PBVC and GMV, at 0-12 months PBVC, GMV and T2-LV, at 0-24 months PBVC and GMV, at 0-36 months PBVC, GMV and T2-LV, and at 0-48 PBVC predicted the differences between the RCSP and Stable groups. PBVC and LVV showed the strongest ability to differentiate patients who presented 0 or >or=3 relapses in the Stable group. Decline in PBVC and GMV were predictive markers of disability deterioration. Correlation of T2-LV with clinical status was weaker and decreased over time. Higher number of relapses was associated with faster decline in whole brain volume.
Keywords: dospělí; Magnetic Resonance Imaging; Recurrence; prednison; Female; azathioprin; Adult; ženské pohlaví; mozkové komory; longitudinální studie; relabující-remitující roztroušená skleróza; interferon beta; lidé; Nerve Fibers, Myelinated; magnetická rezonanční tomografie; recidiva; interferon beta 1a; Prednisone; následné studie; mozek; prognóza; atrofie; Azathioprine; Interferon-beta; Follow-Up Studies; Male; progrese nemoci; Atrophy; Brain; Interferon beta-1a; Multiple Sclerosis, Relapsing-Remitting; Disease Progression; kombinovaná farmakoterapie; Prognosis; Cerebral Ventricles; mužské pohlaví; nervová vlákna myelinizovaná; Longitudinal Studies; Drug Therapy, Combination; Humans